Failure mode and effects analysis (FMEA) of furniture production: A case study in Kelantan state, Malaysia - Ismail, W.O.A.S.W.; Ahmad, M.F.; Sobri, S.A.; Abdullah, N.A.N.; Kamarudin, N.M.F.N.; Mohamed, M.A.; Hermawan, A.; Boon, J.G.; Norizan, M.N. (2021)
The primary objective of this research is to study the critical region of the local furniture manufacturing company by using a Failure Mode and Effects Analysis (FMEA). At the same time, the study also aims to help the organization to minimize production costs by presenting the preliminary stage of the results of the assessment. Many industries used FMEA as a method to improve the evaluation of the reliability of a production process. The use of FMEA is to analyze the layout characteristics of the planned production process in order to ensure that the final product meets customer requirements and expectations. It uses probabilities of detection and occurrence added with a few severity standards to create a risk priority number (RPN) for rating improvement action considerations. Utilized in both the manufacturing and design processes, they notably help to reduce cost factors with the aid of determining product and process improvements early within the development process while changes are inexpensively and relatedly easy to do. Based on the results, there were two failure modes with a higher RPN. The assessment is deductive as it periodically moves from one source to another. Thus, it can assist the company in improving its manufacturing process by reducing the mistakes that been made by identifying the cause and effect of it.